ASSESSMENT AND POLICY OF ALIGNMENT ECONOMIC ASYMMETRY OF RUSSIAN FEDERATION REGIONS - Rustam M. Ustaev; Valentina N. Parakhina (Вестник Северо-Кавказского федерального университета)
The questions deals with economic asymmetry of Russia regions. Analyzed assessment of regional economic asymmetry. Offers basic steps to align of regional economy.